CEP250 is Required for Maintaining Centrosome Cohesion in the Germline and Fertility in Male Mice - Floriot, Sandrine; Bellutti, Laura; Castille, Johan; Moison, Pauline; Messiaen, Sébastien; Passet, Bruno; Boulanger, Laurent; Boukadiri, Abdelhak; Tourpin, Sophie; Beauvallet, Christian; Vilotte, Marthe; Riviere, Julie; et al. (Frontiers in Cell and Developmental Biology, 2022)
Male gametogenesis involves both mitotic divisions to amplify germ cell progenitors that gradually differentiate and meiotic divisions. Centrosomal regulation is essential for both types of divisions, with centrioles remaining tightly paired during the interphase. Here, we generated and characterized the phenotype of mutant mice devoid of Cep250/C-Nap1, a gene encoding for a docking protein for fibers linking centrioles, and characterized their phenotype. The Cep250-/- mice presented with no major defects, apart from male infertility due to a reduction in the spermatogonial pool and the meiotic blockade. Spermatogonial stem cells expressing Zbtb16 were not affected, whereas the differentiating spermatogonia were vastly lost. These cells displayed abnormal γH2AX-staining, accompanied by an increase in the apoptotic rate. The few germ cells that survived at this stage, entered the meiotic prophase I and were arrested at a pachytene-like stage, likely due to synapsis defects and the unrepaired DNA double-strand breaks. In these cells, centrosomes split up precociously, with γ-tubulin foci being separated whereas these were closely associated in wild-type cells. Interestingly, this lack of cohesion was also observed in wild-type female meiocytes, likely explaining the normal fertility of Cep250-/- female mice. Taken together, this study proposes a specific requirement of centrosome cohesion in the male germline, with a crucial role of CEP250 in both differentiating spermatogonia and meiotic spermatocytes.